LYSIMETRIC QUANTIFICATION OF BIODRAINAGE POTENTIAL OF SOME TREE SPECIES OF SOME TREE SPECIES - SUKHAM MADAAN; SARITA DEVI; O. P. TOKY; VIKENDER KAUR (The Bioscan, 2018)
Cylindrical plastic drums of 2.84 m3 capacity filled with field soil and with a water table observation well were used as a single lysimeter. The overall layout comprised of 24 lysimeters with six treatments i.e. i) Casuarina equisetifolia, ii) Eucalyptus tereticornis clone-10, iii) Melia azedarach, iv) Prosopis juliflora v) Terminalia arjuna and vi) blank lysimeter (control). Tree-to-tree spacing was 5m and edges of the lysimeter drums were 3.60 m apart. Results showed that in trees like Casuarina equisetifolia, Eucalyptus tereticornis and Prosopis juliflora which displayed large leaf area over extended period of time, consumptive water use was maximum as 16.7, 16.3 and 14.0 kL year-1, respectively. Conversely, trees like Melia azedarach and Terminalia arjuna, which were deciduous, the water biodrained was 6.8 and 5.9 kL year-1, respectively. On a seasonal scale ambient temperature (r = 0.750** to 0.902**), pan evaporation (r = 0.557** to 0.906**) and vapor pressure deficit (r= 0.434** to 0.797**) in different tree species were the most influential factors determining quantity of water biodrained. Present findings report a new lysimetric design for the rapid quantification of the biodrainage potential of tree species.